George Rudé (1910-1993) - Rogers, Nicholas (Labour / Le Travail, 1994)
The article pays homage to the life and work of George Rudé, a member of the historians' group of the Communist Party of Great Britain who taught at Concordia and York universities during the later part of his career.
Keywords: 1910-1993; George; RUDE